Interv'iu s Vladimirom Shumeiko . Interv'iu s Vladimirom Shumeiko . Interview with Vladimir Shumeiko . Интервью с Владимиром Шумейко - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Discussion on Russia's political and economic situation. Featured in the program: Shumeiko, Vladimir Filippovich (First Deputy Prime Minister of the Russian Federation); Fedorov, Boris (Deputy Prime Minister of the Government of the Russian Federation) Contributors: Kurkova, Bella Alekseevna (Anchor) О политической и экономической ситуации в Российской Федерации. В программе участвуют: Шумейко, Владимир Филиппович (Первый заместитель председателя Правительства Российской Федерации); Федоров, Борис (Заместитель председателя правительства Российской Федерации) Создатели: Куркова, Бэлла Алексеевна (Ведущий/Ведущая)